Asociación de hiponatremia y resultados clínicos en pacientes con infarto agudo del miocardio del Hospital Regional de Loreto, 2017-2024 - Vasquez Lanchi, Luis Arnulfo (2025)
Objective: To determine the association between hyponatremia and adverse clinical outcomes (mortality, ICU admission, complications, and hospital stay) in patients with acute myocardial infarction treated at the Regional Hospital of Loreto between 2017 and 2024. Methodology: An observational, analytical, cross-sectional study was conducted. A total of 74 patients diagnosed with AMI were included, and serum sodium levels at admission were assessed in relation to adverse clinical outcomes. Results: The mean serum sodium level was 135 mEq/L, with hyponatremia present in 40.5% of patients. This condition was significantly more frequent among those with adverse outcomes (51.1%; p = 0.021). Hyponatremia was associated with a longer hospital stay, with a mean of 5.4 days compared to 3.2 days (p = 0.000), and a sevenfold higher risk of hospitalization for ≥5 days (OR = 7.000; 95% CI: 2.482 19.745; p = 0.000). Additionally, increased risk of adverse outcomes was observed in patients with hyponatremia (OR = 3.286; 95% CI: 1.171–9.222; p = 0.024), male sex (OR = 3.804; p = 0.009), and STEMI (OR = 4.167; p = 0.021). The ROC curve demonstrated a moderate predictive capacity for hyponatremia (AUC = 0.655; 95% CI: 0.528–0.782; p = 0.029), with an optimal cutoff point of 134.3 mEq/L (sensitivity: 52.08%; specificity: 92.31%). Conclusion: Hyponatremia was common among AMI patients and showed a significant association with adverse clinical outcomes and prolonged hospitalization, indicating its moderate utility as a predictive marker.